Diazonium-functionalized laserir-radiated graphene as a material for flexible and wearable electronics; Химия и химическая технология в XXI веке - Lipovka A. A. Anna Anatolyevna; Khalelov A.; Postnikov P. S. Pavel Sergeevich; Dorozhko E. V. Elena Vladimirovna; Sheremet E. S. Evgeniya Sergeevna; Rodriguez Contreras R. D. Raul David (Химия и химическая технология на иностранном языке, 2020)
Заглавие с экрана